2022
DOI: 10.3390/vaccines10030474
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Level and Persistence of Anti SARS-CoV-2 IgG after BNT162b2 Vaccine: Evidence from a Large Cohort of Healthcare Workers

Abstract: We aimed at evaluating quantitative IgG response to BNT162b2 COVID-19 vaccine among health care workers (HCW), and exploring the role of demographic, clinical, and occupational factors as predictors of IgG levels. On May 2021, among 6687 HCW at the largest tertiary care University-Hospital of Northwestern Italy, at a median of 15 weeks (Interquartile range-IQR 13.6–16.0) after second-dose, serological response was present in 99.8%. Seropositivity was >97% in all the subgroups, except those self-reporting im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 37 publications
3
30
3
Order By: Relevance
“…We previously documented a clear inverse association between age and humoral response in our cohort of vaccinated HCW, consistent with literature data [15]; on the other hand, in this study, cellular immunity in terms of responsiveness and level of response was directly correlated with increasing age; other studies performed on HCW found non-significant reduction in T-cell response with increasing age [12,25,38] or even a vaccine-induced CD8+ T cell response enhanced in older males [23]. Although our observation deserves further evaluation, it is likely that pre-existing cross-reactive immune responses could play a role, as previously discussed.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We previously documented a clear inverse association between age and humoral response in our cohort of vaccinated HCW, consistent with literature data [15]; on the other hand, in this study, cellular immunity in terms of responsiveness and level of response was directly correlated with increasing age; other studies performed on HCW found non-significant reduction in T-cell response with increasing age [12,25,38] or even a vaccine-induced CD8+ T cell response enhanced in older males [23]. Although our observation deserves further evaluation, it is likely that pre-existing cross-reactive immune responses could play a role, as previously discussed.…”
Section: Discussionsupporting
confidence: 93%
“…Considering clinical features, the self-reported occurrence of immunodeficiency tended to be associated, although not significantly, with low responsiveness and level of IFN-γ production, as already seen for serology. Similarly, the self-reported occurrence of autoimmune diseases also tended to be associated to lower levels of cellular immunity, whereas no significant association was found for serology in our previous study [15]. Although we have to consider the limit of self-reporting, it is likely that impairment in immune responses in immune-mediated diseases, as well as specific therapies, may play a relevant role in vaccine immunogenicity, as already described for example in multiple sclerosis and immune-mediated inflammatory rheumatic diseases [49][50][51][52][53] or immunodeficiency [54,55].…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations